Nightwork - Roberts, Nora (New York : St. Martins Press, 2022)
"Harry Booth started stealing at nine to keep a roof over his ailing mothers head, slipping into luxurious, empty homes at night to find items he could trade for precious cash. When his mother finally succumbed to cancer, he left Chicago--but kept up his nightwork. Wandering from the Outer Banks to Savannah to New Orleans, he dons new identities and stays careful, observant, distant. He cant afford to attract attention--or get attached. Still, he cant help letting his guard down when he meets Miranda Emerson"--
Keywords: Honor -- Fiction; Thieves -- Fiction; Man-woman relationships -- Fiction; Thrillers (Fiction); Romance fiction; Novels